Moral signaling in startups: how ESG claims shape stakeholder judgments and ethical legitimacy - Chan, Eugene Y. (Journal of business ethics, 2026)
This research investigates how environmental, social, and governance (ESG) strategies shape stakeholder perceptions and funding outcomes for startups, with attention to their ethical implications. Grounded in debates within business ethics, particularly the tension between instrumental and normative motivations for ESG adoption, we investigate whether ESG strategies help startups navigate moral expectations while also building credibility and stakeholder trust. Across four studies—a survey, two survey experiments, and an archival analysis—we test how ESG messaging strength (i.e., the specificity and commitment level), its focus (environmental vs. social), and startup stage (early vs. scaling) affect stakeholder perceptions of authenticity, risk, reward, and support. Study 1 reveals that startups are seen as more innovative but less credible than established companies. Study 2 shows that strong ESG claims bolster stakeholder support, especially for startups, while weak claims backfire. Study 3 finds environmental ESG claims reduce perceived risk for early-stage startups, whereas social claims enhance rewards for scaling ones. Study 4 confirms these effects with Crunchbase data. Findings demonstrate that ethically grounded ESG strategies can strengthen stakeholder engagement and funding success when tailored appropriately.